Comparison of the Accuracy of Capital Asset Pricing Model (CAPM) and Abitrage Pricing Theory (Apt) in Predicting LQ45 Stock Returns: Perbandingan Akurasi Capital Asset Pricing Model (CAPM) dan Abitrage Pricing Theory (Apt) Dalam Memprediksi Return Saham LQ45 - Wati, Alis Setya; Hariyanto, Wiwit (Indonesian Journal of Law and Economics Review, 2018)
This study aims to determine which method is more appropriate in predicting LQ45 stock returns (2015-2017 period). The accuracy of the CAPM method and the APT method is measured by Mean Absolute Deviation (MAD). This research uses quantitative methods with purposive sampling tech- nique. The population used in this study were all company shares listed in the LQ45 Index and obtained 32 shares for the LQ45 Index which was used as the research sample. The accuracy of the CAPM and APT models is measured through MAD (Mean Absolute Deviation), while the independent sample t-test is used to compare the accuracy between the CAPM method and the APT method. The results showed that the CAPM method was more appropriate than the APT method in predicting LQ45 stock returns because the value of MADCAPM was smaller than the average MADAPT, namely MADCAPM (0.0004) < MADAPT 0.0113, and based on the results of different test independent sample t-test with SPSS H0 is rejected and Ha is accepted, there is a difference in accuracy because the Sig value is smaller than the significance level (5%), namely Sig = 0,000 < 0.05.